IDENTIFIKASI CENDAWAN ENTOMOPATOGEN DAN MORTALITAS SERANGGA UMPAN PADA BEBERAPA LAPISAN TANAH DARI PERKEBUNAN KAKAO (Theobroma cacao L.) - Yuliana, Yuliana; Anshary, Alam; Yunus, Mohammad (AGROTEKBIS, 2019)
Cocoa (Theobroma cacao L.) is a plant with high economic value, but in its cultivation technique, is inseparable from pest attack, one of which is cacao fruit borer (Conopomorphacramerella). In an effort to control it, can take advantage of soilborne entomopatogenic fungi found in several layers of soil on cocoa plantations.The aims of this study were to determine the type of entomopathogenic fungi and its effect on bait insects (Chrysalis of C. cramerella). The research took place from August 2017 to completion. Sampling was done at Cocoa Plantation then tested further in Laboratory of Plant and Disease, Agricultur Faculty of Tadulako University.This study used Randomized Complete Design (RCD) method consisting of 3 treatments, namely: Soil on horizon O (L1), horizon A (L2), and horizon E (L3) resectively. Isolation of the fungus was done by using bait insects (Chrysalis of C. cramerella) obtained from the field. Identification of fungi was done macroscopically and microscopically. There are 4 genera of entomopathogenic fungi that can be identified which are Aspergillus, Beauveria, Verticillium and Fusarium.The results showed that the percentage of mortality of test-infected fungi in the horizon O was 20 (100%), A horizon was 20 (100%), and E horizon was 15 (60%).